THE EFFECT OF NURSE THERAPEUTIC COMMUNICATION AND APPLICATION OF PATIENT SAFETY OBJECTIVES ON THE IMAGE OF MEDICAL WORKS HOSPITAL WITH PATIENT TRUST AS INTERVENING VARIABLE - Marcellia, Alvina; Rita, Kemala; Adi Pamungkas, Rian (LP2M IAI Al-Khairat Pamekasan, 2022)
The image is valuable intangible assets from company. Positive image allow a company to get score reputation and excellence competitive. One indicator in formation image something house illness is the existence of good communication and guaranteed patient safety in administering service. In addition to good communication and patient safety during receiving services at the hospital, in the process of assessing the patient's image of the hospital, trust is needed from Patients to Hospitals to be the key main the formation of the image of the hospital Research Objectives: this study aims to analyze influence communication therapeutic and Application Target Patient Safety on Hospital Image with Patient Trust as an intervening variable at Karya Medika Hospital. Research methods: quantitative explanative because to know connection among variables based on previous hypotheses that have been put forward by the researcher earlier. The sample in this study is total sampling, namely post-patient patients stay during the period January-March 2022 totaled 193 people. Analysis technique use analysis path (path analysis). Research results: (1) There are influence positive Among Communication Therapeutic and Application Target Patient Safety on Hospital Image at Karya Medika Hospital through Patient Trust as an Intervening Variable. (2) There are positive and significant influence Among Patient Trust in Hospital Image at Karya Medika Hospital. (3) There are positive and significant influence Among Communication Therapeutic on Hospital Image at Karya Medika Hospital. (4) There are positive and significant influence Among Application Target Patient Safety on Hospital Image at Karya Medika Hospital. (5) There are positive and significant influence Among Communication Therapeutic on Patient Trust in Karya Medika Hospital. (6) There are positive influence Among Application Target Patient Safety on Trust Patients at Karya Medika Hospital.